2003
DOI: 10.1590/s0370-44672003000300010
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of Acid Rock Drainage (ARD) occurrence in a gold mine located in a Southeastern Brazil region

Abstract: This work is aimed at evaluating the potential of Acid Rock Drainage (ARD) from two Brazilian gold sulfidic ore samples, by means of using three of the most traditional ARD prediction techniques: Standard Acid Base Accounting and Modified Acid Base Accounting, as static methods, and humidity cells, as a kinetic method. Samples were submitted to chemical and mineralogical characterization that indicated the presence of traces of sulfide minerals, such as pyrite, arsenopyrite, pyrrhotite and of carbonates, calci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
3
0
2
Order By: Relevance
“…A presença de cádmio, cromo, cobalto, cobre, níquel e chumbo também foi detectada, mas em concentrações menores. [23], que observaram valores elevados de potencial redox favorecem a oxidação de materiais sulfetados, com a decorrente diminuição do pH da água lixiviada. Esse fato está associado ao pH mais elevado do meio, que inibe a oxidação da pirita, reduz a solubilidade dos metais e favorece os processos de adsorção de compostos metálicos na matéria mineral [24,25].…”
Section: Resultsunclassified
“…A presença de cádmio, cromo, cobalto, cobre, níquel e chumbo também foi detectada, mas em concentrações menores. [23], que observaram valores elevados de potencial redox favorecem a oxidação de materiais sulfetados, com a decorrente diminuição do pH da água lixiviada. Esse fato está associado ao pH mais elevado do meio, que inibe a oxidação da pirita, reduz a solubilidade dos metais e favorece os processos de adsorção de compostos metálicos na matéria mineral [24,25].…”
Section: Resultsunclassified
“…However, the presence of slag, in both ratio of the 1:1 and 1:1.5, increased the pH, decreased the Eh, and reduced the concentration of metals and sulfate in the leachate. This condition inhibits the oxidation of pyrite, reduces the solubility of the metal and promotes the adsorption of metal compounds on mineral matter [22][23][24].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, comparative studies between methods have reported different ANC values. For example, Capenema and Ciminelli (2003) identified the modified Sobek method as more accurate when characterising three sulphidic ore samples. Morin (2009) reported that Sobek ANC values when compared to modified methods showed variations (either higher or lower) 40-60% of the time when properly conducted.…”
Section: Acid Base Accountingmentioning
confidence: 99%